IMPLEMENTATION OF SOIL MEDIA IN PAINTING LEARNING TO IMPROVE STUDENT CREATIVITY SMAN 11 GOWA - Saeful Efendi; Soekarno B Pasha; Irsan Kadir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore the use of Natural media in the form of soil as a color pigment in the learning of painting in students of SMAN 11 Gowa, Tombolo Pao District. The background of this research is based on the importance of developing students ' creativity through the utilization of local potential and the use of alternative materials that are economical and environmentally friendly compared to synthetic dyes. As a Adiwiyata school, the utilization of Tombolo Pao local land which has four natural color variants, namely black, brown, red, and yellow, is a relevant learning innovation in fostering aesthetic sensitivity and environmental concern of students. This study uses a qualitative descriptive approach with a focus on the process of exploration of materials, soil processing techniques into painting pigments, and analysis of student work based on physioplastic elements including color, texture, and harmonization. Subjects were students of Class XII language SMAN 11 Gowa who follow the practice of learning the art of painting using soil media on canvas.The results showed that the use of soil media in the learning of painting is able to produce distinctive visual characters in the form of natural textures and shades of earthy tones. This learning process not only improves studentstechnical skills in processing unconventional materials, but also encourages awareness of the value of local wisdom and environmental awareness. Thus, soil media can be used as an innovative alternative in learning the fine arts to develop students creativity on an ongoing basis.